Corpi “in prova”. Petrolio, salute e ambiente nelle indagini della Procura di Siracusa - Falconieri, Irene (Antropologia Pubblica, 2024)
The paper aims to reflect on the connections between environmental activism and health risk in the industrial area of Augusta, Priolo and Melilli (SR). In particular, through the analysis of some criminal proceedings initiated by the Public Prosecutor's Office of Syracuse, we will investigate the ways in which, since the Nineties of the last century, the bodies "sick of pollution" have been subjected to a double process of socialization. Placed within the framework of judicial investigations, they have been objectified and evaluated to become useful evidence to demonstrate any illegal conduct attributed to the petrochemical industries present in the territory. At the same time, despite the fact that no activism of a purely legal nature has been created in the area under investigation, these issues have strongly encouraged the emergence of a public awareness of the environmental and health risks associated with the processes of industrial development. Sick individuals/bodies - actually or potentially - have thus become "social bodies" (Lambert, McDonald 2009) capable of creating new forms of political participation (Petryna 2002).